STRIVING FOR LOVE REFLECTED IN ADAM SHANKMAN'S A WALK TO REMEMBER MOVIE (2002): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SARI, CHANDRA PUSPITA (2010)
This study is aimed to show the striving for love reflected in Adam Shankman's A Walk to Remember movie by using an individual psychological approach. It is done by establishing two objectives: the first is analyzing the movie based on its structural elements and the second is analyzing the movie based on the individual psychological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary data source. The primary data source is the A Walk to Remember movie directed by Adam Shankman released in 2002. While the secondary data sources are other materials taken from books, journals and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, setting, plot, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other and form the unity into good quality of a movie. Second, based on individual psychological analysis, such as Fictional Finalism, Inferiority Feeling and Compensation, Striving for Superiority, Style of Life, Social Interest, and Creative Self by using this method Landon Carter as the major character can solve his problem.